2018
DOI: 10.1155/2018/6962090
|View full text |Cite
|
Sign up to set email alerts
|

Mirizzi Syndrome: Diagnosis and Management of a Challenging Biliary Disease

Abstract: Background Mirizzi syndrome is a condition difficult to diagnose and treat, representing a particular “challenge” for the biliary surgeon. The disease can mimic cancer of the gallbladder, causing considerable diagnostic difficulties. Furthermore, it increases the risk of intraoperative biliary injury during cholecystectomy. The aim of this study is to point out some particular aspects of diagnosis and treatment of this condition. Methods The clinical records of patients with Mirizzi syndrome, treated in the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 15 publications
2
61
0
3
Order By: Relevance
“…In 1991, Tamada et al (12) applied ENGBD to the treatment of acute cholecystitis. Similar reports were followed by Johlin and Neil (13) According to these reports, the success rate of ENGBD was 53.8-90.0% (5,13,15,16). An investigation reported by Masuda et al (17) revealed that the success rate of ENGBD in patients with no acute inflammation was 75.6% (90/119) and 71.0% (22/31) in patients with acute cholecystitis and Mirizzi syndrome, which was slightly low.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In 1991, Tamada et al (12) applied ENGBD to the treatment of acute cholecystitis. Similar reports were followed by Johlin and Neil (13) According to these reports, the success rate of ENGBD was 53.8-90.0% (5,13,15,16). An investigation reported by Masuda et al (17) revealed that the success rate of ENGBD in patients with no acute inflammation was 75.6% (90/119) and 71.0% (22/31) in patients with acute cholecystitis and Mirizzi syndrome, which was slightly low.…”
Section: Discussionmentioning
confidence: 53%
“…Because of the difficulty of preoperative diagnosis and the complexity of pathological changes in patients with Mirizzi syndrome, laparoscopic treatment for the disease is difficult and is associated with high risk for complications (4,5). It has been reported that patients with Mirizzi syndrome have a high rate of conversion from LC to open cholecystectomy (1).…”
Section: Discussionmentioning
confidence: 99%
“…Pablo Luis Mirizzi was one of the best biliary surgeons of the last century; he was the first surgeon to perform an intraoperative cholangiography successfully. Nonetheless, we usually recognize him by the syndrome that is named after him [ 1 , 2 ]. In 1948 he described the condition in with an impacted stone in the gallbladder infundibulum causes jaundice by extrinsic compression of the common bile duct [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gallstone disease and its complications are among the most common surgical interventions worldwide; the arrival of better diagnostic and treatment modalities has improved patient outcomes [ [1] , [2] , [3] ]. Although gallstone disease is generally associated with cholecystitis, rare events such as Mirizzi syndrome can represent a challenge for the biliary surgeon, as they can significantly increase the risk of intraoperative biliary injury [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation